Design and performance of an X‐ray scanning microscope at the Hard X‐ray Nanoprobe beamline of NSLS‐II. (4th October 2017) - Nazaretski, E.; Yan, H.; Lauer, K.; Bouet, N.; Huang, X.; Xu, W.; Zhou, J.; Shu, D.; Hwu, Y; Chu, Y. S.
Abstract : A multilayer Laue lenses based X‐ray scanning microscope installed at the Nanoprobe beamline of the National Synchrotron Light Source II is described. Abstract : A hard X‐ray scanning microscope installed at the Hard X‐ray Nanoprobe beamline of the National Synchrotron Light Source II has been designed, constructed and commissioned. The microscope relies on a compact, high stiffness, low heat dissipation approach and utilizes two types of nanofocusing optics. It is capable of imaging with ∼15 nm × 15 nm spatial resolution using multilayer Laue lenses and 25 nm × 26 nm resolution using zone plates. Fluorescence, diffraction, absorption, differential phase contrast, ptychography and tomography are available as experimental techniques. The microscope is also equipped with a temperature regulation system which allows the temperature of a sample to be varied in the range between 90 K and 1000 K. The constructed instrument is open for general users and offers its capabilities to the material science, battery research and bioscience communities.